Associations between residential greenness and blood lipids in Chinese Uyghur adults. (September 2020) - Fan, Shujun; Yang, Bo-Yi; Xue, Zhenxiang; Huang, Wen-Zhong; Zhou, Ziyan; Yuan, Jun; Wang, Yuzhong; Zhong, Yi; Tang, Xiaoping; Dong, Guanghui; Yang, Zhicong; Zhang, Zhoubin
Highlights: The first study to examine the effect of greenness on blood lipids in rural areas. Higher greenness exposure was associated with lower TG and higher HDL-C levels. Higher greenness exposure was associated with lower odds of hypoalphalipoproteinemia. The associations were stronger in women or those with higher education level. Abstract: Background: Dyslipidemia is a major risk factor for cardiovascular disease. Several studies have explored the associations of greenness with blood lipids. However, the evidence is still limited and mixed, especially in rural areas. Methods: From May to September 2016, we recruited 4735 Uyghur adults from rural areas of northwestern China. We measured levels of total cholesterol (TC), triglycerides (TG), high-density lipoprotein cholesterol (HDL-C), and low-density lipoprotein cholesterol (LDL-C). Two satellite-derived vegetation indices — Normalized Difference Vegetation Index (NDVI) and Soil Adjusted Vegetation Index (SAVI) — were used to estimate residential greenness levels. The associations between exposure to residential greenness and blood lipids levels and dyslipidemia prevalence were examined using the Generalized Linear Mixed Models. Results: Living in greener areas was associated with lower TG levels, higher HDL-C levels, and lower odds of hypoalphalipoproteinemia (e.g., per 0.20-unit increase in NDVI100 m was associated with 0.02 mmol/L (95% CI: 0.001, 0.03) higher levels of HDL-C and 0.87-fold (95% CI: 0.77, 0.98) lower odds of hypoalphalipoproteinemia). These associations remained in a series of sensitivity analyses. Stratified analyses showed that the associations of NDVI100 m with LDL-C and HDL-C levels were stronger in women and in participants with higher education level. Conclusions: Higher greenness exposure was beneficially associated with blood lipids among rural Uyghur population in China, especially among women or those with higher education level.